LAS CIUDADES INTERMEDIAS COMO OBJETO DE ESTUDIO EN EL MARCO DEL CAPITALISMO PERIFÉRICO: EL MÉTODO COMO CONSTRUCCIÓN DE CONOCIMIENTO - Omar Arrieta Chavarría (Geo UERJ, 2019)
This article starts from the idea of the method as a processing of construting of knoeledge in the geographical research of the urban space in intermediate cities located on the periphery of the periphery of global capitalism. The  analysis uses some of the contributions of three convergent theoretical-methodological perspectives within critical thinking that, in my view, are essential to develop the  research on geographical space in general and about  the spatial forms assumed by the uniqueness of small towns on the periphery of the capital accumulation axes, which leads us to analyze the inequalities and socio-spatial fragmentation of the territory, the transformations in urban morphology and the cultural changes generated by the globalization of the capitalist market in its most specific manifestations at the local level which constitute the object of study of this essay. Those three approaches are: first, theories that work on complexity from a critical perspective; second, the critical epistemology of Latin American configurationism; and third, the neo-Marxist approach to urban studies. The study succinctly develops some concepts and indicators that in the "reconstruction of theory" were empirically investigated in the city of Liberia in the province of Guanacaste, Costa Rica, Central America.